Choices and Voices: The Influence of Voice Pitch on the Voting Preference of Barangay Tubod, Iligan City - Capa, Allen Dave; Lariosa, Charish Ann; Pacaldo, Renalyne; Iglupas, John Gieveson; Aguja, Hilton; Baulete, Elaine (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This study explores the role of voice pitch as a heuristic influencing voting preferences and leadership-related impressions. Drawing from the case of 200 respondents from Barangay Tubod, Iligan City, this study determines the influence of voice pitch on voting preference and leadership-related impressions. A face-to-face survey was conducted to identify their preferred male and female voice pitch in a hypothetical Philippine presidential election as well as the male and female voice pitch that respondents tend to associate with the leadership attributes of dominance, intelligence, competence, strength, and trustworthiness. An individual face-to-face interview was further conducted to identify the reasons and impressions of the voter respondents’ preferred female and male voice pitches to further reinforce the quantitative findings. Results showed that the low- pitched female and male presidential candidates in a hypothetical election are significantly preferred by voter respondents. Interestingly, young adult respondents did not have any significant preference for any voice pitch of the female candidate which differs from the prior works of literature on voting preference associated with voice pitch.